Comparison of the oxidation behavior of a zirconium nitride coating in water vapor and air at high temperature. (1st July 2018) - Gao, Zhaohe; Chen, Ying; Kulczyk-Malecka, Justyna; Kelly, Peter; Zeng, Yi; Zhang, Xinxin; Li, Chun; Liu, Han; Rohbeck, Nadia; Xiao, Ping
Highlights: The parabolic rate constant of ZrN oxidizing in water vapor environment at 600 °C was 100 times faster than that in air. The bilayer-structure of ZrO2 with t-ZrO2 near ZrN-ZrO2 interface and outer m-ZrO2 were formed after steam or air oxidation. The lateral cracks across the ZrO2 scale were caused by the phase transition from t-ZrO2 to m-ZrO2 . Abstract: The oxidation behavior of zirconium nitride coating in high-temperature water vapor and air environments was studied. The parabolic rate constant of ZrN oxidizing in the water vapor environment at 600 °C was approximately 100 times faster than that in air, due to the larger pores and greater number of cracks that were formed across ZrO2 oxide layer formed during the water vapor oxidation process than during the air oxidation process. A bilayer-structure ZrO2 with tetragonal ZrO2 near the ZrN/ZrO2 interface and monoclinic ZrO2 approaching the outer ZrO2 surface were formed in both cases. The lateral cracks across the ZrO2 scale were caused by volume expansion from the tetragonal ZrO2 phase to the monoclinic ZrO2 phase transition.